The influence of educational status on motor performance and learning: a literature review - Mariana Callil Voos; Letícia Lessa Mansur; Fátima Aparecida Caromano; Sonia Maria Dozzi Brucki; Luiz Eduardo Ribeiro do Valle (Fisioterapia e Pesquisa, 2014)
Many studies have shown the impact of the educational status on cognitive and motor control. However, few studies in the area of Physical Therapy and Motor Behavior consider the educational status of the subjects. This study aimed to describe evidences about the influence of the educational status on motor behavior (and its repercussions on physiotherapeutic assessment) and on motor learning (and its repercussions on physiotherapeutic treatment). We included in this review national and international studies from 1998 to 2013 from SciELO, MEDLINE and LILACS databases. We used the keywords: educational status, schooling level, motor control, motor behavior, motor performance, and motor learning. Sixty studies were located and 28 were selected, because they followed the inclusion criteria: (1) to investigate the effect of education on motor performance; (2) be available in Portuguese or English; and (3) be available in Brazil. The review showed that the educational status of patients must be considered by the physiotherapists in experimental and clinical practice, because many studies have shown its influence on assessment and treatment of young and older adults.